Digitization, copyright, and the law copyleft and the future of intellectual property - Lombardi, Ettore Maria (Routledge, Taylor & Francis Group, 2025)
"This book discusses copyleft and its impact on the traditional way to conceive of property. It is specifically focused on the European and International juridical framework. Analysing the impact of digitalization on copyright and the potential effect of copyleft in the European market and within a European and International juridical framework, this book explores the complex evolutionary framework which charts the reduction of physical property and the progressive expansion of intangible assets. Although digitalisation enables more accessibility than ever before, this impacts traditional intellectual property frameworks. Evaluating common traits of ownership structure, the book considers the challenges that intangible property, open source and creative commons present to the current legal system. Examining the impact of copyleft on copyright and the law of ownership, the book considers the rights of authors and creators, legal limits and complications arising from these new forms of ownership of intangible assets the book is grounded in the European potential regulatory framework of copyleft through movements like open-source software. The book will be of interest to students, academics and practitioners with an interest in Contract Law, Property Law and Intellectual Property Law"
Keywords: Copyright licenses; Copyright and digital preservation; Copyright / Electronic information resources; Copyright and electronic data processing; Open source software / Law and legislation; Intellectual property